2010
DOI: 10.1007/s12035-010-8109-5
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Amyloid-β and Tau Pathologies on Mitochondria In Vivo

Abstract: The histopathological characteristics of Alzheimer’s disease (AD) are amyloid-β (Aβ) containing plaques and neurofibrillary tangles (NFTs) as well as neuronal and synaptic loss. Until today, the underlying mechanisms of the interplay of plaques and tangles remained unresolved. There is increasing evidence that mitochondrial dysfunction might be a possible link, as revealed by studies in several APP and tau transgenic mouse models. Recently, we examined mitochondrial function in a novel triple transgenic mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 71 publications
0
102
0
Order By: Relevance
“…The fact that alterations in mitochondrial distribution are evident at early stages, in the 5.5 month rTg4510, supports the notion that transport deficits and accompanying mitochondrial changes in distribution are early events in neurodegenerative cascades. 19,23,24,42,43 Several potential mechanisms for tau overexpression contributing to transport deficits have previously been explored. (1) Studies of tau over-expression in cells and in vitro assays have demonstrated negative consequences to anterograde cellular transport, by directly inhibiting progress of kinesin-1, by forming a "road block" on the microtubule where excessive tau is bound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that alterations in mitochondrial distribution are evident at early stages, in the 5.5 month rTg4510, supports the notion that transport deficits and accompanying mitochondrial changes in distribution are early events in neurodegenerative cascades. 19,23,24,42,43 Several potential mechanisms for tau overexpression contributing to transport deficits have previously been explored. (1) Studies of tau over-expression in cells and in vitro assays have demonstrated negative consequences to anterograde cellular transport, by directly inhibiting progress of kinesin-1, by forming a "road block" on the microtubule where excessive tau is bound.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Furthermore, tau over-expression in vitro has been shown to result in increased mitochondrial fragmentation, alterations in mitochondrial membrane potential, impaired calcium buffering and oxidative stress responses, and diminished respiratory chain function. 19,43,52 For these reasons, we assessed mitochondrial volumes in the 8.5 month-old rTg4510 and nonTg mice to determine whether concomitant disequilibrium in fission and fusion dynamics is evident alongside mitochondrial distribution deficits. We did not find significant differences in mitochondrial size in the neuropil, which is consistent with a proteomic study of P301L mutant tau over-expressing mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysfunctional mitochondria produce high levels of reactive oxygen species (ROS); these ROS can negatively affect specific mitochondrial components, including mitochondrial DNA (mtDNA), membrane lipids, and oxidative phosphorylation proteins [18,19]. For example dysregulation of complex I has been correlated with tau toxicity, and dysregulation of complex IV has been associated with increased Aβ load [20][21][22]. Additionally, specific proteins are affected by mitochondrial dysfunction in AD, including amyloid precursor protein, presenilin 1 and presenilin 2, which reside along the mitochondria-associated endoplasmic reticulum membranes [23].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, nine different mitochondrial haplogroups have been identified (H, I, J, K, T, U, V, W and X). This lead to a suggestion that inherited European mitochondrial haplogroups may be related to longevity, as well as AD risk in Caucasians [4, 11,12].…”
Section: Mitochondrial Genetics and Admentioning
confidence: 99%